Effects of trench‐perpendicular ridge subduction on accretionary wedge deformation: Clues from analogue modelling. (24th August 2018) - Wang, Chunyang; Ding, Weiwei; Li, Jiabiao; Dong, Chongzhi; Fang, Yinxia; Tang, Limei; Ma, Letian; Zhao, Yanghui; Cheng, Zihua
Abstract : Basement highs (e.g., seamounts and ridges) often exist on subducted oceanic plates. However, their effects on the deformation of accretionary wedges have not been well understood, in particular the sequential cross‐sectional evolutionary processes caused by ridge subduction. To evaluate the effects of ridge subduction on accretionary wedges, analogue models were run to observe the deformation processes in both plan and cross‐sectional views. The results show that ridge subduction induces an inverted‐U‐shaped uplifted area, while seamount subduction always causes a circular uplifted area in plan view. Both ridge and seamount subduction will result in a radial fan‐shaped strike‐slip fault system in plan view, with opposite slip directions of the faults in the two wings. During ridge subduction, the faults in the left wing of the ridge axis are sinistral, and those in the right are dextral, which is reverse to that of seamount subduction. This may result from the backward flow in the overlying sediments during the rapid subsidence in the wake of the seamount, which would reverse the initial movement along the strike‐slip faults. The subducted ridge induces migration of wedge material from the frontal margin to the distal part, expressed by changes in structural geometry and kinematics (e.g., reduction in wedge length and taper angle and increase in wedge height). The accretionary prism adapted to the variation of taper angle by the development of back‐thrust faults and out‐of‐sequence thrust fault. Our model results shed lights on understanding the interior structural deformation pattern and mechanism caused by natural cases of ridge subduction, such as Gagua Ridge and North d'Entrecasteaux Ridge.